Secrets of word-of-mouth marketing : how to trigger exponential sales through runaway word of mouth - Silverman, George, 1942- (American Management Association, 2011)
The first edition of The Secrets of Word-of-Mouth Marketing provided readers with step-by-step guidance for constructing a word-of-mouth marketing campaign that would penetrate successive audience tiers and build sales exponentially. Extensively revised to reflect the profound changes in the marketplace, from new attitudes and communication methods, to new ways of relating to increasingly wary Web 2.0 customers, the second edition of this groundbreaking book shows readers how they can move beyond traditional approaches to inspire the kind of word of mouth that catches fire and generates revenue. Featuring enlightening case studies and examples, as well as an updated version of the author's innovative Decision Matrix for identifying potential buyers and determining and crafting the right kind of message, The Secrets of Word-of-Mouth Marketing simplifies the process of choosing the delivery method, harnessing the power of influencers, and measuring results. From how to navigate the latest digital media to what Malcolm Gladwell got wrong, this is still the last word on word of mouth.